Melanotic spinothoracic schwannoma. Issue 2 (April 1979) - Paris, F; Cabanes, J; Muñoz, C; Tamarit, L
Abstract : A dumb-bell mediastinal melanotic schwannoma is described, and the rarity of this type of tumour emphasised. The tumour was resected by simultaneous laminectomy and posterior thoracotomy. The patient is well four years after operation. The pathology of the tumour is described and the origin of melanotic cells is discussed.